The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1046/j.1365-246x.2000.00035.x
|View full text |Cite
|
Sign up to set email alerts
|

VARNET-96: influence of the Variscan and Caledonian orogenies on crustal structure in SW Ireland

Abstract: Summary VARNET, an international multidisciplinary project, was designed to examine the ‘Variscan Front’ in the southwest of Ireland. As part of the seismic experiment a 200 km long wide‐angle seismic profile (Line A) was recorded from the Old Head of Kinsale in the south of Ireland to Galway Bay on the west coast. Along Line A, 170 seismic stations were deployed at approximately 1 km intervals. Results from ray trace modelling indicate a multilayered crust. The upper crust, extending to a depth of about 14 km… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(72 citation statements)
references
References 35 publications
6
65
1
Order By: Relevance
“…The Irish continental shelf and many of the basins therein have been the focus of seismic reflection, seismic refraction and potential field investigations for several decades (Holder & Bott 1971;Whitmarsh et al 1974;Bunch 1979;Jacob et al 1985;Makris et al 1988;Roberts et al 1988;Lowe & Jacob 1989;O'Reilly et al 1991O'Reilly et al , 1995O'Reilly et al , 2010Vogt et al 1998;Landes et al 2000Landes et al , 2003Morewood et al 2005;Hauser et al 2008). Coupled with sparse well control, the resulting studies have allowed for the piecing together of the detailed tectonostratigraphic basin evolution of the margin (Shannon 1991;Naylor & Shannon 2009.…”
Section: The Irish Atlantic Marginmentioning
confidence: 99%
“…The Irish continental shelf and many of the basins therein have been the focus of seismic reflection, seismic refraction and potential field investigations for several decades (Holder & Bott 1971;Whitmarsh et al 1974;Bunch 1979;Jacob et al 1985;Makris et al 1988;Roberts et al 1988;Lowe & Jacob 1989;O'Reilly et al 1991O'Reilly et al , 1995O'Reilly et al , 2010Vogt et al 1998;Landes et al 2000Landes et al , 2003Morewood et al 2005;Hauser et al 2008). Coupled with sparse well control, the resulting studies have allowed for the piecing together of the detailed tectonostratigraphic basin evolution of the margin (Shannon 1991;Naylor & Shannon 2009.…”
Section: The Irish Atlantic Marginmentioning
confidence: 99%
“…Also, very little is known about the deep structure of this fault zone. A northward dipping reflector on the BIRPS seismic profile due west of the Shannon Estuary has been interpreted as the structural trace of the ISZ [Klemperer, 1989], while Lowe and Jacob [1989] and Landes et al [2000] Abramovitz et al [1999] concluded that, based on seismic evidence, the ISZ formed due to anti-clockwise rotation of the Eastern Avalonian continent, and subsequent drift and subduction of Laurentia under Eastern Avalonia, with a south-dipping reflector in the upper mantle [Landes et al, 2000].…”
Section: Pages 337340-341mentioning
confidence: 99%
“…During theVARNET-96 controlled source exper iment in southern Ireland [Masson et al, 1999;Landes et al, 2000], teleseismic P-waves from distant earthquakes and nuclear test explosions were also recorded. A significant anomaly in the variation of P-wave travel time residuals of magnitude about 1.0 s co-incide with the pos tulated surface trace of the Caledonian ISZ.…”
Section: Pages 337340-341mentioning
confidence: 99%
“…The Munster Basin is generally considered to have evolved as an E–W‐orientated half‐graben comprised of thick Devonian sediments (Husain 1957; Todd 1989; Williams et al 1989). The presence of outcropping sediments to the south of the Killarney–Mallow Fault Zone indicates that down‐to‐the‐south displacement occurred on the fault and a southerly dip is inferred for this structure (Landes et al 2000; Vermeulen et al 2000). Variscan inversion may explain the presence of shallow upper crust in the hangingwall of the Killarney–Mallow Fault Zone.…”
Section: Geological and Tectonic Settingmentioning
confidence: 99%
“… Fence diagram of the crust and upper mantle structure of the southwest of Ireland using available onshore and offshore seismic refraction/wide‐angle reflection data recorded in the period of 1982–1996. The VARNET‐96 profiles (Masson et al 1998; Landes et al 2000), COOLE85‐P1 (Lowe & Jacob 1989) and COOLE85‐P6 (O'Reilly et al 1991) were deployed perpendicular to the E–W Variscan trend while the ICSSP82 (Jacob et al 1985), COOLE85‐P7 (along the axis of the North Celtic Sea Basin; O'Reilly et al 1991) and COOLE85‐P3a (Makris et al 1988) profiles run approximately parallel to strike of the predominant NE–SW Caledonian trend. ICSSP82 intersects both line A and COOLE85‐P1.…”
Section: Introductionmentioning
confidence: 99%